Features of right making in the activity of the judiciary - Філик, Н. В.; Калістратов, О. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Authors examine the legal conflicts that arise in the process of court lawmaking and analyze the featuresof legal technology of court acts.